A Review of Beef Production Systems for the Sustainable Use of Surplus Male Dairy-Origin Calves Within the UK - Rutherford, Naomi H.; Lively, Francis O.; Arnott, Gareth (Frontiers in Veterinary Science, 2021)
The UK dairy herd is predominantly of the Holstein-Friesian (HF) breed, with a major emphasis placed on milk yield. Subsequently, following years of continued single-trait selection, the beef production potential of dairy bred calves has declined. Thus, male HF calves are commonly seen as a by-product of the dairy industry. Limited markets, perceived low economic value and high rearing costs mean that these surplus calves are often euthanised shortly after birth or exported to the EU for further production. Welfare concerns have been raised regarding both euthanasia and long distance transportation of these calves. Furthermore, total UK beef consumption increased by 8.5% from 2009 to 2019. Thus, in light of this growing demand, beef from the dairy herd could be better utilized within the UK. Therefore, the potential for these calves to be used in a sustainable, cost-effective beef production system with high welfare standards within the UK requires investigation. Thus, the aim of this review was to evaluate both steer and bull beef production systems, examining the impact on performance, health, welfare, and economic potential to enable a sustainable farming practice, while meeting UK market requirements. The principal conclusions from this review indicate that there is the potential for these calves to be used in UK based production systems and meet market requirements. Of the steer production systems, a 24 month system appears to achieve a balance between input costs, growth from pasture and carcass output, albeit the literature is undecided on the optimum system. The situation is similar for bull beef production systems, high input systems do achieve the greatest gain in the shortest period of time, however, these systems are not sustainable in volatile markets with fluctuating concentrate prices. Thus, again the inclusion of a grazing period, may increase the resilience of these systems. Furthermore, production systems incorporating a period at pasture are seen to have animal welfare benefits. The main welfare concern for surplus dairy bred calves is often poor colostrum management at birth. While in steer systems, consideration needs to be given to welfare regarding castration, with the negative impacts being minimized by completing this procedure soon after birth.